KNOWLEDGE, ATTITUDES AND PRACTICES OF AL-RAFIDAIN UNIVERSITY COLLEGE’S STUDENTS TOWARDS SMOKING (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Cigarette smoking remains a major public health concern worldwide, particularly among young adults and university students, and one of the leading preventable causes of morbidity and mortality worldwide.Objectives: To estimate the Knowledge, attitudes and practice towards smoking, and finding the source of information about smoking in Al-Rafidain University College’s students.Method & Subjects: This is a cross-section study through online survey, a questionnaire designed through Google form, and by distributed the electronic link to students’ telegrams channels of the Al-Rafidain university college. The study conducted from 25/9/2024 -25/1/2025.Results: Five hundred and thirty-four students enrolled in this study, through online survey about smoking. The highest percent 336(62.9%) in the age group 20 and below, females 342(64.0%), in the second stage 271(50.7%), never married 504(94.4%), most participants think they had moderate monthly income 339(63.5%), living in urban 517(96.8%). The majority of students 516(96.6%)
Keywords: smoking, college-students, knowledge, attitude, Cigarrete, Electronic cigarrete, nargileh, Baghdad, Iraq.